Prostaglandin Receptor Signaling in Disease - Toshiyuki Matsuoka; Shuh Narumiya (The Scientific World Journal)
Prostanoids, consisting of the prostaglandins (PGs) and the thromboxanes (TXs), are a group of lipid mediators formed in response to various stimuli. They include PGD2, PGE2, PGF2α, PGI2, and TXA2. They are released outside of the cells immediately after synthesis, and exert their actions by binding to a G-protein coupled rhodopsin-type receptor on the surface of target cells. There are eight types of the prostanoid receptors conserved in mammals from mouse to human. They are the PGD receptor (DP), four subtypes of the PGE receptor (EP1, EP2, EP3, and EP4), the PGF receptor (FP), PGI receptor (IP), and TXA receptor (TP). Recently, mice deficient in each of these prostanoid receptors were generated and subjected to various experimental models of disease. These studies have revealed the roles of PG receptor signaling in various pathological conditions, and suggest that selective manipulation of the prostanoid receptors may be beneficial in treatment of the pathological conditions. Here we review these recent findings of roles of prostanoid receptor signaling and their therapeutic implications.